Origin, frequency, and variability of protostylid in human populations from southwestern Colombia: a systematic literature review - Hernández-Silva, Jesús Alberto; Moreno-Correa, Sandra; Moreno-Gómez, Freddy (Revista Facultad de Odontología Universidad de Antioquia, 2015)
Introduction: protostylid is a non-metric dental trait observable on the vestibular surface of first and second deciduous and permanent molars in populations of Mongoloid origin. The objective of this literature review was to identify the expression of protostylid in human populations from Southwestern Colombia to help clarify the macro-evolutionary processes in this geographic region. Methods: a systematic literature review in PubMed, Google Scholar, and SciELO using the following medical descriptors: “dental morphology”, “non-metric dental traits”, and “protostylid”, combined with the Boolean operators “+” and “&” by the PRISMA methodology, in order to find publications describing the prevalence and variability of protostylid in human populations from Southwestern Colombia by means of the Arizona State University Dental Anthropology System. Results: 11 publications were found allowing us to obtain biological matrix distances based on cluster hierarchical classification and their respective dendrograms using the Ward method, which allowed us to observe most of the populations in Southwestern Colombia considered in this study and their relationships with other world populations. Conclusions: miscegenation processes have influenced the prevalence of protostylid, decreasing the expression of groove, blunt vertex cusp, and free vertex cusp in indigenous populations, and increasing the expression of fossa or P point in mixed coastal populations and populations of African descent. It also became clear that the expression of fossa or P point can occur in the absence or presence of protostylid.